Do types of information in an animated video intervention affect university students' knowledge of autism spectrum disorder (ASD) and openness towards peers with ASD in Singapore? - Lee, Raelene Shu Xuan (Nanyang Technological University, 2023)
As more students with Autism Spectrum Disorder (ASD) are enrolling in universities in recent years, it is crucial that the general student population has adequate knowledge and awareness of ASD to provide a supportive and conducive environment for students with ASD to learn in. This pre-test post-test control group design sought to compare the effectiveness of delivering different types of information/video condition ([1] factual information vs. [2] factual information + descriptive and explanatory information vs. [3] factual information + descriptive, explanatory + directive information) in an animated video intervention in increasing university students’ knowledge and openness toward peers with ASD. The sample consisted of 92 undergraduates (27 males, 65 females; age range = 18 - 36) from various local universities in Singapore. Participants were randomly assigned to one of the three experimental conditions, where they completed a measure of their knowledge of ASD and openness scale, before viewing a 5-minute long animated video containing different types of information about ASD. After which, participants completed the measure of knowledge of ASD and openness scale again, followed by a measure of their empathy level. Results indicated that participants’ ASD knowledge improved following the viewing of the animated video. However, the three different videos containing different types of information did not differ in influencing participants’ openness toward individuals with ASD. Nevertheless, qualitative responses proposed that the video containing factual information, with descriptive, explanatory, and directive information was useful in helping participants to know how to interact with individuals with ASD. The findings of this study provide preliminary support for the most effective method to educate and raise awareness about special educational needs, such as ASD, among the general student population in order to foster a supportive and inclusive environment. Keywords: Autism Spectrum Disorder, special educational needs, university students, Autism Spectrum Disorder knowledge, openness, intervention, animated video